CORRELATION BETWEEN ACADEMIC STRESS AND STUDENT’S ORGANIZATIONAL PERFORMANCE IN SCHOOLS OF PUBLIC HEALTH AND LIFE SCIENCES: A CROSS-SECTIONAL STUDY - Guntur A. Gama Muhammad; Syahrul Ramadhan; Syifa’ul Lailiyah; Shinta Feby Ningtyas; Farhaiza Ramadhania (Journal of Community Mental Health and Public Policy, 2023)
Background: The difficulties in balancing student academic duties, organizational activities and social life results in stress that may affect organizational performance. Purpose: The aim of the study was to determine the relationship between academic stress in students and student organizational performance. Methods: This is a cross-sectional study of 91 public health students of the School of Health and Life Sciences Universitas Airlangga. Depression Anxiety Stress Scale (DASS 42) questionnaires which was distributed via Google form. Chi-square test was used to analyse the data. Results: Most respondents (49.4%) had normal levels of academic stress, 16 students (18.4%) had moderate stress, 15 students (17.2%) had mild stress, 8 students (9.2%) had severe and 5 students (5.7%) very severe. In addition, the results obtained were that the majority of respondents had good performance in the organization, namely 46 students or 52.9%, moderate performance of 37 students or 42.5%, excellent as many as 2 students or 2.3%, poor performance of 1 student or 1.1% and worse performance of 1 student or 1.1%. Conclusion: The results of the interpretation of the data obtained for a p value of 0.003 which means there was a relationship between academic stress and student performance in organizations. Abstrak Latar Belakang: kesulitan dalam menyeimbangkan tugas akademik, aktivitas organanisasi dan kehidupan sosial mengakibatkan stress yang dapat mempengaruhi kinerja organisasi. Tujuan: penelitian untuk mengetahui hubungan antara stres akademik pada mahasiswa terhadap kinerja mahasiswa berorganisasi. Metode: Penelitian ini adalah studi cross-sectional pada mahasiswa 91 mahasiswa Sekolah Ilmu Kesehatan dan Ilmu Alam Universitas Airlangga. Depression Anxiety Stress Scale (DASS 42) yang disebarkan melalui google form. Uji untuk menganalisis data penelitian menggunakan uji chi-square. Hasil: diperoleh responden mayoritas memiliki tingkat stres akademik yang normal yaitu 43 mahasiswa atau 49,4%, sedang sebanyak 16 mahasiswa atau 18,4%, ringan sebanyak 15 mahasiswa atau 17,2%, parah sebanyak 8 mahasiswa atau 9,2% dan sangat parah sebanyak 5 mahasiswa atau 5,7%. Selain itu diperoleh hasil bahwa responden mayoritas memiliki kinerja yang baik dalam organisasi yaitu 46 mahasiswa atau 52,9%, kinerja cukup baik sebanyak 37 mahasiswa atau 42,5%, sangat baik sebanyak 2 mahasiswa atau 2,3%, kinerja kurang baik sebanyak 1 mahasiswa atau 1,1% dan kinerja sangat kurang baik sebanyak 1 mahasiswa atau 1,1%. Kesimpulan: Hasil interpretasi data yang didapatkan untuk nilai p sebesar 0,003 yang berarti ada hubungan yang antara stres akademik dengan kinerja mahasiswa dalam berorganisasi.